Challenges and Opportunities for Applying Philosophical Values in Christian Religious Education - Ndaparoka, Yefta ibrahim; Fallo, Abryani; Langkola, Adinda Lestari; Tanono, Solly Rosalia; Tateni, Sandro (Jurnal Ilmiah Mandala Education (JIME), 2025)
This research aims to analyze philosophical values in Christian religious education by identifying the challenges and opportunities faced by developing a literature study method which uses a research approach by collecting, analyzing and summarizing information from various written sources, journals, articles and documents related to education. Christian religion. The results of this research are to inform or show the values of applying philosophy in Christian religious education, in facing challenges with the application of these values such as limited resources, global cultural influences, technological challenges and limited understanding.Even though there are many challenges faced, there are opportunities that Christian religious education can take advantage of. Christian religious education has the potential to instill strong moral and ethical values through a critical approach to religious teachings by integrating philosophical principles such as love, justice and truth. The integration of philosophical values in Christian religious education can provide positive value in improving the quality of learning and character development of students in the modern era. Apart from that, Christian religious education can also form individuals who are responsible and moral and provides a deep understanding of faith and the purpose of life.